Instability of a Fifth-Order Nonlinear Vector Delay Differential Equation with Multiple Deviating Arguments - Cemil Tunç (Journal of Mathematics)
We study a fifth-order nonlinear vector delay differential equation with multiple deviating arguments. Some criteria for guaranteeing the instability of zero solution of the equation are given by using the Lyapunov-Krasovskii functional approach. Comparing with the previous literature, our result is new and complements some known results.